2013
DOI: 10.1111/apt.12534
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with network meta‐analysis: pharmacological prophylaxis against post‐ERCP pancreatitis

Abstract: SUMMARY BackgroundThe efficacy of many pharmacological agents for preventing post-ERCP pancreatitis (PEP) has been evaluated in randomised controlled trials (RCTs), but it is unclear which agent(s) should be used in clinical practice. Network meta-analyses of RCTs are used to simultaneously compare several agents to determine their relative efficacy and identify priority agents for comparison in future RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 76 publications
2
39
0
4
Order By: Relevance
“…Treatment has been unsatisfactory with the exception of the use of rectal nonsteroidal anti-inflammatory drugs (NSAIDs) and prophylactic pancreatic stents. A network meta-analysis based on existing randomized controlled trials (RCTs) showed that rectal NSAIDs are one of the most efficacious agents for preventing PEP [4]. However, prophylactic stent placement is not cost-effective in patients at average risk for the development of PEP [5].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment has been unsatisfactory with the exception of the use of rectal nonsteroidal anti-inflammatory drugs (NSAIDs) and prophylactic pancreatic stents. A network meta-analysis based on existing randomized controlled trials (RCTs) showed that rectal NSAIDs are one of the most efficacious agents for preventing PEP [4]. However, prophylactic stent placement is not cost-effective in patients at average risk for the development of PEP [5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, at least 48 randomized controlled studies have been reported utilizing 15 different agents with most studies including patients at average or mixed risk for post-ERCP pancreatitis. At least six studies included high-risk patient populations [30]. Drugs that have been evaluated and their efficacy are listed in Table 3.8.…”
Section: Can a Pill Prevent Post-ercp Pancreatitis?mentioning
confidence: 99%
“…There are some data suggesting that topical nitroglycerin might be beneficial. Based on a recent network meta-analysis of very limited data involving diagnostic ERCP, topical epinephrine may reduce post-ERCP pancreatitis [30].…”
Section: Can a Pill Prevent Post-ercp Pancreatitis?mentioning
confidence: 99%
“…Interestingly, a network meta-analysis showed that rectal NSAIDs were superior to pancreatic duct stenting and was not inferior to the combination of rectal indomethacin and prophylactic pancreatic stent placement for the prevention of post-ERCP pancreatitis [27]. A more recent network meta-analysis concluded that topical epinephrine and rectal NSAIDs were the most efficacious agents in preventing post-ERCP pancreatitis [28].…”
Section: Prevention Of Post-ercp Pancreatitismentioning
confidence: 99%
“…Perforation is a life-threatening event; prompt recognition and efficient management are very important [28]. Patients should have nothing by mouth and be administered with adequate intravenous fluids (and nutrition as necessary), and are usually given antibiotics.…”
Section: Sphincterotomy-related Perforationmentioning
confidence: 99%